PRACTICAL CONTEXTS OF NATIONAL SECURITY ON THE PARTNERSHIP CONDITIONS: POSITIVE EXTERNALS AND EFFICIENCY OF SECURITY - VIVVHAR, Oksana; MURAVSKA, YULIYA; GEVKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The dynamic development of scientific thought suggests that armed conflicts pose a significant threat to humanity due to the possible expansion of the number of participants in globalization, the development of environmental disasters, the negative humanitarian consequences associated with the growing number of refugees. The issue of resolving armed conflicts is relevant and occupies an important place in the system of modern international relations.NATO's involvement in the settlement of armed conflicts is a comprehensive and systematic set of measures aimed at building long-term and sustainable peace, establishing the rule of law, protecting human rights and freedoms, and uniting society around a common development strategy. The international legal mechanisms for NATO's participation in the settlement of armed conflicts are based on a coherent strategy, taking into account the interests of all citizens; they cannot be used by anyone to achieve personal goals. It should be noted that a post-conflict settlement, being fair, restores citizens' trust in the state, its bodies and institutions, and establishes mutual understanding and mutual respect.The scientific issue of Ukraine-NATO cooperation as an important mechanism for combating hybrid warfare is particularly relevant and complicated. However, the security is a key point. The aim of the article is to present specific features of non-military cooperation between Ukraine and NATO. Based on the long-term goal of joining to the European system of collective security, Ukraine is building new approaches to ensuring national security. The purpose of this article is to review the literature topic, as well as the current situation of Ukraine-NATO cooperation, the hybrid warfare, as well as additional and alternative forms of security policy. In this paper we attempt to determine the factors of Ukraine-NATO cooperation, the conditions, the advantages and disadvantages of current solutions, as well as the conclusion of present situation with the issuance of diagnosis for the future mechanism for combating hybrid warfare. The article uses the reports and results of selected studies conducted in Ukraine.
Keywords: NATO - Ukraine cooperation; hybrid warfare; security; national security; international security